JIG DESIGN FOR MOTORIZED SPINDLE ATTACHMENT OF 3-AXIS VERTICAL MACHINING CENTER - Aulia Dewangga, Rifqie
One type of machine tool that is commonly used is a VMC (Vertical Machining Center) machine with 3 axes of motion orientation. VMC machines have limitations, especially in some cases where the machining process must be carried out with the spindle axis orientation horizontally. A spindle attachment design is now available which will operate horizontally. To ensure the accuracy of the spindle attachment installation, a jig design for the spindle attachment will be carried out in this undergraduate project. The design begins with making the design requirements & objectives. Then do the manufacturing and modeling of alternative designs. In this design there are 3 alternative designs. Next, 1 best design will be selected from 3 alternative designs. Furthermore, the selected design will be examined for its accuracy level based on ISO 1701-2 using the stack tolerance analysis method. Then the static stiffness test is carried out using simulation software, and finally the selected design manufacturing process will be compiled so that it has an accuracy level that meets the standard. The results of the design selection show that alternative design 2 is the best design. The results of the static test design 2 show a good value of static stiffness. Furthermore, the results of the tolerance pile analysis on alternative design 2 show that alternative design 2 has an accuracy level that meets ISO 1701-2 standards. And a manufacturing process that allows to achieve this level of accuracy has been devised.